The fortunes of history of infrastructure in Colombia: the case of the tunnel of the line (2015)
The Case of the line tunnel is one of the most important projects in the history of infrastructure in Colombia This is the case, that to build a road to intercept the national epicenter with the main Colombian Pacific port, the national government initiated a feat that bear serious risks in terms, geological, hydrological volcanological well. Hence the birth of the so called work "CROSSING THE CENTRAL MOUNTAINS: TUNNELS II CENTENNIAL - TUNNEL AND SECOND LINE CALZADA Calarca - CAJAMARCA" The great importance of this project lies in improving economic processes in the Region and the country, causing a reduction in costs and time to transport cargo to the port of the country, a project which was embroiled in legal and financial disputes, because the deadlines and resources to carry it out were insufficient to the contractor, on the type of contract as the work was signed.